IMPLEMENTASI TUGAS, KOMPETENSI, DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH DASAR (studi kasus di 11 SD swasta) - Laura F.N. Sudarnoto (Universitas Bunda Mulia, 2015)
The success or failure of any organizations including education institution depends on the leader behavior. A school principal needs to play their role as a leader and manager in order to create conducive learning environment. The task of school principal consist of planning programs and academic activities; in the process, some factors that become barriers include: 1) planning such as teachers, financial, time, administration works, and external influence; 2) monitoring and evaluation of all activities, the implementation of learning process, financial, students’ mentoring, and teachers’ assistance; 3) follow up of improvement or development, for finding solution and re-evaluate. Some competencies that compulsory to be a school principal are managerial competency, pedagogic, intellectual competency, personality and social competency. The instrument of this research was open –ended questionnaire that had been answered by school principals and also a grading scale that had been filled by primary school teachers. This research used descriptive narrative analysis and comparative analysis. The results gained from case studies among 11 private primary schools. It revealed that school principals tend to use transformational leadership style rather than transactional leadership style. Keywords: competency, leadership style, transformational leadership behavior, transactional leadership behavior